Validation of Fluorescence Activated Cell Sorting (FACS) procedures for use in pre-clinical modeling and clinical sample diagnostics in Peripheral Artery Disease (PAD) - Pentakota, Ananya (East Carolina University, 2023)
Peripheral artery disease (PAD) is a vascular condition caused by atherosclerosis in the peripheral arteries, most commonly the ones supplying blood to the lower extremities. Chronic limb threatening ischemia (CLTI) is the most severe clinical PAD presentation and carries a high risk of major amputation or death. Little advancement in treatment options have been made, creating a dire need to find alternatives. The lab studies PAD in order to better understand the mechanisms of the disease and develop therapies for patients. The lab strongly values understanding the microenvironment of the ischemic limb, which consists of a heterogenic mix of cell types. An effective way to study the role each cell type requires individual isolation. This calls for the establishment of a fluorescence-activated cell sorting (FACS) protocol to be used for cell specific isolation in pre-clinical and clinical samples. This procedure will consist of tissue harvest, cell isolation, antibody staining, and FACS. The findings from this project not only validates the use of FACS for sample diagnostics, but it also starts the investigation of cell specific contributions to ischemia. These results will aid in the creation of new cell specific precision medicine therapies for PAD.
Keywords: PAD; FACS; Physiology